Organoleptic, rheological and crystallization properties of confectionery glaze with beet powder - E. V. Mazukabzova; L. V. Zaytseva (Пищевые системы)
The recipe composition of confectionary glaze determines its high caloricity upon the low content of physiologically significant substances. Introduction of fruit and vegetable raw materials makes it possible to increase a content of dietary fibers, vitamins, macro- and microelements in a product, as well as to reduce an amount of added sugar. This paper considers a technological possibility of introducing vegetable powders into the confectionary glaze recipe by the example of the beet powder. Physico-chemical indicators of the beet powder were studied in comparison with the classic recipe components of confectionary glaze. An effect of an amount of the beet powder (3–15%) introduced instead of part of sugar on the organoleptic, rheological and crystallization properties of glaze was studied. Organoleptic evaluation revealed that addition of the beet powder into the confectionary glaze recipe in an amount of more than 15% led to appearance of floury off-flavor. It was found that yield strength of glaze increased in the direct proportion to the content of beet powder in its composition (from 3.601 Pа to 4.446 Pa) and its value was in a range of the optimal values of 3÷7 Pа. Therefore, addition of the beet powder in an amount of up to 15% will not lead to technological difficulties. The study of the kinetics of the process of confectionary glaze structuring showed that addition of the beet powder led to a decrease in the solidification point and an increase in the time of glaze crystallization. The main crystallization parameters of the developed glaze were established: solidification point Tmax=28.0÷28.3°C, crystallization time τmax=8.2÷8.6 min. Based on the performed research, the following recipes were developed: vegetable-containing confectionary glaze with the beet powder content of 3 to 10%; vegetable confectionery glaze with the beet powder content of 13%.